If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b + -43 = 21 Reorder the terms: -43 + b = 21 Solving -43 + b = 21 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '43' to each side of the equation. -43 + 43 + b = 21 + 43 Combine like terms: -43 + 43 = 0 0 + b = 21 + 43 b = 21 + 43 Combine like terms: 21 + 43 = 64 b = 64 Simplifying b = 64
| 19.5=p+4.5 | | k-4=40 | | q/4=3 | | n-92=-45 | | 7(1+4n)=-133 | | 6r-s+9r-3s= | | 15.2=4u | | 3j=87 | | -10-x=2(2+3x) | | 17=f+7 | | p-3=12.34 | | 5.6=2q | | (-5)(-18)= | | 6x-39=195-7x | | 1/25=5x | | Sin(2x)=2sin(x) | | 146=2(d+261) | | -3x-8+6x+10= | | -9-4n=3(2n+1) | | 12a+6a=9 | | s-1.75=6.25 | | 13-x=13+2x | | 16x^4-255X^2=-1008 | | X-5-3x+6= | | 11x+13=46 | | -44=-4(2+3v) | | 2m-4=9m-25 | | 2x+8x+7=0 | | -3(p+2)=-p-1-1p | | 3k-1+7k=10+1-k+8k | | -7x+5-4(x-1)=-4x-(6x-3)+4 | | p+4=14+6p |